The marketing research of the level of promoting the rational use of medicines by pharmacists in Ukraine: uk. - Zhadko, S. V.; Pestun, I. V.; Zavadska, N. P.; Senkiv, N. M. (Social Pharmacy in Health Care, 2021)
Aim. To conduct the marketing analysis of the frequency and causes of the irrational use of medicines according to the assessment of the Ukrainian pharmacists, participation of pharmacists in promoting the rational use of drugs, and identifying appropriate measures to improve the situation. Materials and methods. To achieve this goal, a survey of pharmacists from different regions of Ukraine was conducted, 420 questionnaires were selected and processed. Results. According to pharmacists, such types of the irrational use of drugs as false self-medication, polypharmacy, and the use of expensive drugs in the presence of cheaper alternatives are the most common in Ukraine. The most important reasons for this phenomenon are uncontrolled self-medication, the impact of advertising and the availability of many over-the-counter medicines. The Ukrainian pharmacists take certain measures to influence on the rational use of drugs: refusal to dispense medicines, supplement to the doctor’s prescription, correction of the duration of treatment, and others. When counseling pharmacy visitors the largest number of respondents provide information on the way, frequency and duration of taking a medication, the smallest part – recommendations for a healthy lifestyle or non-pharmacological recommendations for the treatment. The respondents consider compliance with the rules of dispensing prescription medicines, training and advanced training of pharmacists throughout their professional career, and limitation of excessive advertising of medicines as the most appropriate measures to promote the rational use of medicines. Conclusions. The results of the research reflect the peculiarities of the Ukrainian pharmacy practice regarding the participation of pharmacists in promoting the rational use of medicines. Key words: rational use of medicines; pharmaceutical care; pharmaceutical consulting; good pharmacy practice.